PERANAN MASJID DALAM PROSES ISLAMISASI MASYARAKAT ABANGAN: STUDI KASUS MASJID AL-YAQIN DUSUN TAMBAK RUJI - Putri Wulansari (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2019)
The mosque is not just become a spiritual symbol, especially for Muslims. But being a cultural symbol of the country even among Indonesian society. The significance of the role of the mosque does not necessarily make the mosque continues able to maintain eksitensinya in performing various functions, especially in the era of digitalization has the longer and grind the existence and role of the mosque. However, the prestige of the generous nature proficiency level applies only to the community of town with remarkable mobalitas while mosques perkampunngan or rural region still has a significant role in terms of both spiritual and social community. By karenya, this paper discusses the role of Al-Yaqin in the process of Islamization of society initially Hamlet Pond Trellis are Abangan, where a person’s beliefs about Islam, but the dominance kejawenya very thick. In addition, this paper also presented conflicts as a result of diadakanya process of Islamization.